New Indolyl‐Arylaminopropenone Conjugates: Synthesis, Cytotoxicity and Apoptotic Inducing Studies. Issue 6 (13th February 2020) - Adil Shareef, Mohd; Ganapathi, Thipparapu; Khan, Irfan; Rani, Sunitha; Rajanna, Ajumeera; Akbar, Syed; Kumar, C. Ganesh; Babu, Bathini Nagendra
Abstract: In view of the antiproliferative potential of indoles and aryl amino propenones, a series of indolyl tethered aryl aminopropenones have been synthesized and investigated for their anti‐proliferative activity against selected human cancer cell lines. These compounds exhibited good to moderate activity against the tested cell lines. Among them, (Z)‐1‐(1‐(4‐chlorobenzyl)‐1 H ‐indol‐3‐yl)‐3‐((3, 4, 5‐trimethoxyphenyl)amino)prop‐2‐en‐1‐one (6a ) and (Z)‐1‐(1‐benzyl‐1 H ‐indol‐3‐yl)‐3‐((3, 4, 5‐trimethoxyphenyl)amino)prop‐2‐en‐1‐one (6g ) exhibited promising IC50 values of 2.3 μM and 1.9 μM, respectively, against MCF‐7 (human breast cancer cell line). The morphological studies indicated that compounds showed a dose dependent decrease of viable cells in MCF‐7 cell line. The flow cytometric analysis of these potential compounds revealed that they caused cell cycle arrest at G0/G1 phase. Furthermore, Annexin‐V FITC study revealed that the potential compounds induced cell death by apoptosis. In addition, molecular docking studies of the most potential compounds provided insights about the binding interactions of the compounds with Bcl‐2 protein. Abstract : A series of indolyl tethered aryl Aminopropenones were synthesized and evaluated for their antiproliferative potential. Among them, (Z)‐1‐(1‐(4‐chlorobenzyl)‐1 H ‐indol‐3‐yl)‐3‐((3, 4, 5‐trimethoxyphenyl)amino)prop‐2‐en‐1‐one (6a ) and (Z)‐1‐(1‐benzyl‐1 H ‐indol‐3‐yl)‐3‐((3, 4, 5‐trimethoxyphenyl)amino)prop‐2‐en‐1‐one (6g ) exhibited promising cytotoxicity, caused cell cycle arrest at G0/G1 phase and induced cell death by apoptosis. The most potential compounds also exhibited binding interactions with Bcl‐2 protein.